Analisis Bahan Ajar PAI Kelas VII Sampai Kelas IX Tingkat SMP Berbasis Teknologi Informasi Dan Komunikasi - Herman Ahmad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
Facing the era of digitalization that continues to advance rapidly, the world of Islamic education is required to continue to innovate in order to balance the progress of the world, so that Islamic education can be relevant to the situation, on the other hand so that it does not lag behind world progress. Therefore, concrete steps are needed to create a learning activity based on information and communication technology. The method used in the preparation of this article is field research.